(untitled) (Revista Eixos Tech, 2023)
Prevalence estimates in the last few decades make autism the fastest-growing neurodevelopmental disability. Autistic symptoms usually lead to significant impairment in social communication, repetitive behavior patterns, and, possibly, fixed and restricted interests. This work aimed to review the recent literature to synthesize and provide a straightforward understanding of the autism etiology, evidencing estimates regarding its prevalence, heritability, and recurrence rates. Taking research with refined methodologies, large populations, multiple geographical areas, and well-known diagnostic procedures, the results show significant variability in prevalence (overall: 1.1-2.1%, females: 0.5-0.9%, males: 1.8-3.6%). Studies that investigated larger sample sizes show overall recurrence rates among siblings of ? 9-10% (females: ? 4-5%, males: ? 14-18%). In comparison, studies that explored relatively small sample sizes presented a higher recurrence with larger variation (overall: ? 14-27%, females: ? 9-20%, males: ? 26-32%). The Broader Autism Phenotype (BAP) recurrence rates also presented higher variation, from 10% to 55% at ? 36 months of age. Adding autism and BAP estimates, the overall risk for developmental concerns in high-risk siblings ranged from ? 27% to ? 77% (overall: ? 50%, females: ? 32%, males: ? 60%). Heritability data also vary, although studies that explored large and diverse samples and applied robust heritability estimation methods pointed to relatively stable estimates, from ? 80% to ? 85%.